Plan de marketing turístico para el Parque Universitario de Educación Ambiental y Recreacional “Francisco Vivar Castro” «puear» del cantón Loja – provincia de Loja - Garrochamba Alulima, Johnny David (2016)
The development currently presents the national tourism has taken hold in the last decade, the Ministry of Tourism has identified a wide range, with a number of cultural and natural attractions for different types of tourists, becoming diverse country, when it comes to natural attractions, Ecuador is a privileged country for being the largest diversity 〖Km〗 ^ 2, where mainly stands the Yasuni National Park, which was designated by UNESCO in 1989 as a biosphere reserve; for many years protected areas have not had a proper handling of the promotion and dissemination, also the city of Loja, musical and cultural capital of Ecuador, which has environmental characteristics of exceptional beauty located in its consolidated areas however is not found highly developed, as is the case of Parque Universitario de Educación Ambiental y Recreación “Francisco Vivar Castro” "PUEAR" which despite its characteristics, these elements are not known by the Lojana citizenship because they have a limited advertising by the lack of a marketing plan that generates tourism activities in this sector from becoming absent and unable to create a competitive market space. Given this situation arises, the present investigation reflecting the negative impact of the lack of dissemination, and thus aims to increase the educational and recreational activities in University Park, constituting a significant contribution to formulate guidelines for the promotion of their potential by developing a marketing plan after the respective diagnosis, which is structured with 3 objectives which are to develop an advertising plan, plan for training local guides and recommendations for the development of architectural readjustment plan, while the proposal with the local authorities in order to obtain approval for the implementation of this project was socialized. This research work was conducted at the Universidad Nacional de Loja, addressed to the administrative authorities thereof, wherein the following methods and techniques were used: Inductive and deductive method was useful for analyzing general problem identified in the University Park and thus arriving at the respective conclusions which gave way to propose appropriate recommendations in order to increase the number of visitors to the site. The descriptive method was used to explain the problem and the proposed solutions to University Park, in the same way it served to expose the important properties of the same, about infrastructure and biodiversity features, from precise measurements of events. In addition to carrying out the work of respective field took into account the survey and interview, the same as after sampling went to a certain group of people, where he studied and gathered information that helped solve the problem of research and so determined and quantified variables related to the draft. It also took into account direct observation, by direct observation sheet could identify the facts of PUEAR, and thus detect the potential that has the same This information will be socialized with the authorities of University Park and people interested in the development and conservation of the same, revealing the new alternatives to promote and disseminate to which you can access. Based 5 on the diagnosis several marketing strategies and tactics aimed at strategic SWOT matrix to allow positioning the park as a representative icon of the town were raised. Once this investigative work completed is set to consider the different experiences in the conceptualization and data collected leading to the elaboration of some conclusions about the investigation developed, also recommendations encourage the search for alternatives that contribute to are pointed promoting the place; and finally they attached several annexes which consist of photographs, scanner, records, documents… which show the work done. Hoping that the spread of University Park is a project to contribute to its development, it is expected to generate new alternatives for recreation and strengthening education.